Предмет: Алгебра,
автор: ruthkhkz
Х4+16х2+64completely
Ответы
Автор ответа:
1
x⁴+16x²+64
x^2•2+2•x²•8+8²
(x²)²+2•x²•8+8²
a²+2ab+b²= (a+b)²
(x²+8)²
Автор ответа:
0
x^4 + 16x^2 + 64.
По формуле a^2 + 2ab + b^2 = (a + b)^2:
(x^2 + 8)^2.
По формуле a^2 + 2ab + b^2 = (a + b)^2:
(x^2 + 8)^2.
Похожие вопросы
Предмет: Математика,
автор: adelili2002
Предмет: Русский язык,
автор: юляша30
Предмет: Литература,
автор: jartem2005
Предмет: Биология,
автор: Nasti12
Предмет: История,
автор: star120
x^2 + 8 = 0
x^2 = -8
x = 2i*sqrt(2).